Integrating production scheduling and vehicle routing decisions at the operational decision level: A review and discussion. (February 2017) - Moons, Stef; Ramaekers, Katrien; Caris, An; Arda, Yasemin
Highlights: A review of integrated production scheduling–vehicle routing problems is provided. A production-distribution classification matrix is presented. Simple production and distribution environments are mostly considered. Integrated studies with more real-life characteristics are necessary. Fast and robust solution approaches for integrated studies need to developed. Abstract: Production scheduling and vehicle routing are two well-studied problems in literature. Although these supply chain functions are interrelated, they are often solved sequentially. This uncoordinated approach can lead to suboptimal solutions. In the current competitive business environment, companies are searching for methods to save costs and improve their service level. Integrating production and distribution scheduling operations can be an approach to improve the overall performance. This paper focuses on integrated production-distribution operational level scheduling problems, which explicitly take into account vehicle routing decisions of the delivery process. Existing literature on integrated production scheduling and vehicle routing problems is reviewed and classified. Both the problem characteristics of mathematical models and the accompanying solution approaches are discussed to identify directions for further research.